Can Ability, Commitment and Motivation Improve Employee Performance? - Ulfa Hidayati (Jurnal Economic Resource, 2021)
The performance of employees at the Ministry of Religion of Maros Regency found several problems, such as the low quality of services that can be directly felt by the public. The research data, the authors use 2 (two) methods, namely: descriptive analysis and qualitative analysis using multiple linear regression models. The results of the partial test show that the ability variable has a positive and significant effect on employee performance during the Pandemic Period at the Ministry of Religion, Maros Regency. The commitment variable has a negative and insignificant effect on employee performance at the Ministry of Religion, Maros Regency. The motivation variable has a positive but not significant effect on employee performance at the Ministry of Religion, Maros Regency. If the commitment and motivation are also appropriately implemented, even though the results of the F-test and T-test show that commitment does not have a positive effect on performance and motivation, it has a positive but not significant effect, but it can be a supporter of the employee's ability to be implemented. Employees at the Ministry of Religion of Maros Regency need strong motivation to maintain their ability to work, especially with the Pandemic situation, which requires more problem-solving in completing work that has experienced many obstacles in the last two years.